2015
DOI: 10.1371/journal.pone.0121178
|View full text |Cite
|
Sign up to set email alerts
|

A Rhizosphere-Associated Symbiont, Photobacterium spp. Strain MELD1, and Its Targeted Synergistic Activity for Phytoprotection against Mercury

Abstract: Though heavy metal such as mercury is toxic to plants and microorganisms, the synergistic activity between them may offer benefit for surviving. In this study, a mercury-reducing bacterium, Photobacterium spp. strain MELD1, with an MIC of 33 mg . kg-1 mercury was isolated from a severely mercury and dioxin contaminated rhizosphere soil of reed (Phragmites australis). While the whole genome sequencing of MELD1 confirmed the presence of a mer operon, the mercury reductase MerA gene showed 99% sequence identity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 53 publications
(53 reference statements)
0
21
0
Order By: Relevance
“…Some of the identified CRT may play important roles in nutrient cycling and the breakdown of toxic compounds in aquaria. In terrestrial soils, some Photobacterium species are rhizosphere-associated symbionts that play a key role in nitrogen cycling (49). The family Rhodobacteraceae is comprised of several hundred described species, including many marine members, and phylogenomic evidence suggests that this group plays an important role in diverse biogeochemical cycles (50).…”
Section: Resultsmentioning
confidence: 99%
“…Some of the identified CRT may play important roles in nutrient cycling and the breakdown of toxic compounds in aquaria. In terrestrial soils, some Photobacterium species are rhizosphere-associated symbionts that play a key role in nitrogen cycling (49). The family Rhodobacteraceae is comprised of several hundred described species, including many marine members, and phylogenomic evidence suggests that this group plays an important role in diverse biogeochemical cycles (50).…”
Section: Resultsmentioning
confidence: 99%
“…Masoor-93 to cope with salt stress [120]. Salt-stressed Arabidopsis plants treated with volatile organic compounds (VOCs) from B. amyloliquefaciens GB03 showed higher biomass production and less Na + accumulation compared to salt-stressed plants without VOC treatment [121].…”
Section: Salinitymentioning
confidence: 99%
“…Canola seeds inoculated with Kluyvera ascorbata SUD165 and grown under gnotobiotic conditions in the presence of high concentrations of nickel chloride were partially protected against nickel toxicity because the bacteria could lower ethylene-induced stress due to nickel toxicity [128]. Photobacterium halotolerans MELD1 facilitated the phytoprotection of Vigna Unguiculata Sesquipedalis against Hg at a concentration of 25 ppm, thus increasing productivity as well as reducing the translocation of Hg to the bean pods [121]. A plant-microbe phytoremediation system was created with the combination of vetiver grass and the functional endophytic bacterium Achromobacter xylosoxidans F3B for the removal of toluene in Ho et al [129].…”
Section: Water Stress Resistancementioning
confidence: 99%
“…Though they are found to be primarily associated with marine environments ( 1 ), Photobacterium halotolerans MELD1 was isolated from the rhizosphere of a terrestrial weed, Phragmites australis , found growing in mercury- and dioxin-contaminated land located near the seacoast ( 2 ). In our previous study, we demonstrated that P. halotolerans MELD1 helped with the phytoprotection of Vigna unguiculata from mercury stress ( 2 ). To gain insight into the genetic traits among the closely related P. halotolerans strains, whole-genome sequencing of terrestrial environment dwelling P. halotolerans MELD1 was performed.…”
Section: Genome Announcementmentioning
confidence: 99%
“…The whole-genome draft of P. halotolerans MELD1 consists of 57 contigs for a total of 4,758,037 bp with an overall G+C content of 51%, 258 pseudogenes, 17 rRNA genes, and 88 tRNA genes. In our previous work, we identified the presence of a merA gene and its mercury reductase activity, as well as resistance to toxic compounds like cadmium, lead, and dioxin ( 2 ). As a trait of adaptation to the mercury-contaminated habitat, the genome of MELD1 contains a mer operon containing a mercury reductase gene ( merA ).…”
Section: Genome Announcementmentioning
confidence: 99%